2003
DOI: 10.1093/jee/96.3.879
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Leafrollers (Lepidoptera: Tortricidae) from Organic and Conventional Orchards to Azinphosmethyl, Spinosad, and Bacillus thuringiensis

Abstract: Populations of obliquebanded leafroller, Choristoneura rosaceana Harris, and three-lined leafroller, Pandemis limitata Robinson, were obtained from seven sites in the Okanagan and Similkameen Valleys of British Columbia and assayed for their responses to three insecticides using a leaf disk bioassay. Lethal concentration ratios (LCRs) were calculated for all populations compared with a susceptible laboratory colony of C. rosaceana; significant variation was detected in response to all three insecticides. LCRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The 48 h and 72 h LC 50 values of spinosad to second‐instar larvae of this pest were as low as 0.41 mg kg −1 and 0.35 mg kg −1 respectively. This suggestion is in keeping with that of Burkness et al 20 and Smirle et al ,21 who have reported high toxicity of spinosad to lepidopteran pests. Besides the toxic effect, the present study revealed numerous sublethal effects of spinosad on H. armigera .…”
Section: Discussionsupporting
confidence: 91%
“…The 48 h and 72 h LC 50 values of spinosad to second‐instar larvae of this pest were as low as 0.41 mg kg −1 and 0.35 mg kg −1 respectively. This suggestion is in keeping with that of Burkness et al 20 and Smirle et al ,21 who have reported high toxicity of spinosad to lepidopteran pests. Besides the toxic effect, the present study revealed numerous sublethal effects of spinosad on H. armigera .…”
Section: Discussionsupporting
confidence: 91%
“…These differences reßect the usage pattern of insecticides under organic and conventional management. IPM strategies can impact the susceptibility of pests to insecticides, regardless of which class they belong to, which has been documented elsewhere (Smirle et al 2003). Spinosad was the Þrst spinosyn insecticide registered for use against C. rosaceana in 1998.…”
Section: Discussionmentioning
confidence: 89%
“…Apple growers usually manage leafrollers with insecticides which has selected for resistance and cross-resistance to some classes of compounds (Pree et al 2001;Dunley et al 2006). In order to counter this selection pressure, many growers have broadened their management tactics to include use of microbial and newer conventional insecticides (Cossentine et al 2003;Smirle et al 2003;Sial et al 2010). Meanwhile, researchers have examined the use of sex pheromones for mating disruption (MD), including formulations targeting several species (Evenden et al 1999;Curkovic and Brunner 2005;Judd and Gardiner 2008).…”
Section: Introductionmentioning
confidence: 99%